Modul Psikoedukasi : Pencegahan dan Penanganan Pelecehan Seksual Terhadap Anak - Zahra, Almaira Aura; Putri, Anggi Khoiriyyah; Amalya, Layla Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This psychoeducatioal module is designed to provide practical guidance to adults in preventing and responding to child abuse. With a focus on positive parenting and affective communication, the module addresses types of abuse, signs of child victimization, and family-based prevention and treatment strategies. Approaches include individual and group interventions, communication skills training, and education based on current scientific literature. The module also offers evaluation techniques, such a pre-test, post-test, and in-depth interviews to measure its effectiveness. Implementation results showed significant improvements in participants’ understanding, attitudes and skills in protecting children from abuse. By providing practical tools and evidence-based insights, the module is expected to create a safe and supportive environment for optimal child development.